KAJIAN PENERAPAN MODEL C45, SUPPORT VECTOR MACHINE (SVM), DAN NEURAL NETWORK DALAM PREDIKSI KENAIKAN KELAS - LUSI ARIYANI (Faktor Exacta, 2016)
. Evaluation of the result from student’s studies could be an expectation for the student to go to the next step to continue the next grade at vocational high school. Too many subject ate to be done by students. From the result of the subject which being tested, school can get the average, then school will decided their students can continue to the next grade or not. The prediction for decided about students can go to the next grade or not till this time still in manual and data takes by the result from the end of semester. All predection almost the same with classification which will happen in the future it can be a constraint for the school to manage the rank to solve how to decided about the rank level for the student. The constraint can be solved with analysis which using 3 algorithm C45, algorithm Support Vector Machine and Neural Network. From the result of the research with analysis three of them we’ll know that algorithma Support Vector Machine have high in accuration. Then we can use in class to solve the predection problem abaout students up to the next grade. Keywords: the students, next grade, Algorithm C45, Algorithm Support Vector Mechine, Neural Network.